(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2025)
In recent years, the rapid development of information technology has been accompanied by a surge in cybersecurity issues. Among the various cyberattack methods, phishing stands out as one of the most common and deceptive techniques. Unlike many technical attacks, phishing relies heavily on human psychology and user inattention. This paper presents a detailed overview of phishing attacks and compares them with other prevalent forms of cyberattacks.